MONTELUKAST IN TREATING ALLERGIC DISEASES - T.V. Kulichenko (Union of pediatricians of Russia, 2006)
Anti inflammatory medications are the basis for pathogenetic treatment of allergic diseases. The review covers description of the most studied and efficient medication of leukotriene receptors' antagonist category montelukast. Specific and reversible antagonism to leukotriene receptors sets two most important effects of this medication: treatment of inflammatory process and influence tu muscular cells of bronchi. The article reviews in detail the possibility of applying montelukast in allergology as a basis therapy, peculiarities of its pharmacokinetics, pharmacodynamics and safety. Its advantages and disadvantages for monotherapy of bronchial asthma and allergic rhinitis are discussed, as well as the role of this category of medications in combined therapy of bronchial asthma and allergic rhinitis, and its influence to exercise induced bronchoconstriction.Key words: antagonists of leukotriene receptors, montelukast, bronchial asthma, allergic rhinitis, treatment, children.